Minat Beli Customer Pada Toko Tenun Ikat di Jepara: Studi Kasus Pada Customer Toko Tenun Ikat - Fauziyah, Rika Mellatul; Setiawati, Ira; Gultom, Henry Casandra (STIE Widya Manggala, 2024)
The research was conducted with the aim of analyzing Electronic Word of Mounth (E-WOM), Trust, Quality of Service on Buying Interest in Online Shopping at Ikat Weaving Shop (Case study on Ikat Weaving Shop customers). The method used is quantitative using primary data. Respondents in this study were 97 consumers. The analysis tool used is multiple linear regression analysis with the help of the SPSS Version 26 program. The results of this study show that, Electronic Word of Mounth (E-WOM) has no effect on buying interest, Trust affects Buying Interest and Quality of Service affects Buying Interest.